Pseudoaneurysm Accompanied by Crowe Type IV Developmental Dysplasia of the Hip: A Case Report. (8th May 2012) - Yo, Hirotake; Ohashi, Hirotsugu; Inori, Fumiaki; Okajima, Yoshiaki; Matsui, Yoshio; Shintani, Kosuke
Abstract : We report the case of a 72-year-old woman whose pseudoaneurysm was difficult to diagnose and treat. The patient had a history of congenital dislocated hip and was undergoing anticoagulation therapy with warfarin due to the mitral valve replacement. Her chief complaint was pain and enlargement of the left buttock, and the laboratory tests revealed severe anemia. However, her elderly depression confused her chief complaint, and she was transferred to a psychiatric hospital. Two months after the onset of the symptoms, she was finally diagnosed with a pseudoaneurysm by contrast-enhanced CT and angiography. IDC coils were used for embolization. A plain CT showed hemostasis as well as a reduced hematoma at 2 months after the embolization. The possible contributing factors for the pseudoaneurysm included bleeding due to warfarin combined with an intramuscular hematoma accompanied by Crowe type IV developmental dysplasia of the hip that led to an arterial rupture by impingement between pelvis and femoral head. Since the warfarin treatment could not be halted due to the valve replacement, embolization was chosen for her treatment, and the treatment outcome was favorable.